Is it really safe to replace decabromodiphenyl ether (BDE209) with decabromodiphenyl ethane (DBDPE)?: A perspective from hepatotoxicity. Issue 4 (19th January 2023) - Wang, Yanting; Yang, Yushun; Dang, Chenyuan; Lu, Bin; Luo, Yin; Fu, Jie
Abstract: In this paper, the hepatocytotoxicity and aryl hydrocarbon receptor (AHR) activity of decabromodiphenyl ethane (DBDPE), decabromodiphenyl ether (BDE209) and other 18 analogues were evaluated in vitro using human normal liver cell L02. These dioxin‐like compounds showed differential hepatocytotoxicity (EC50 = 0.38–17.87 mg/L) and AHR activity (EROD activity = 4.53–46.35 U/μg). In silico study indicated the distance of π‐π bonds between the benzene ring of compounds and residue Phe234 of AHR played a key role in the binding of AHR, and the substituents on the benzene ring also influenced the activity. Combining molecular biology and bioomics, the comprehensive investigations on the hepatotoxic mechanisms have demonstrated the AHR signaling pathway was the key mediation mechanism for the hepatotoxicity of DBDPE/BDE209. The cytochrome P450s (CYP2 family) mediated formation of reactive oxygenated intermediates might be the dominant toxic mechanism, which could produce oxidative stress or cause genotoxicity. Although the experimental toxicity of DBDPE was smaller relative to BDE209, the health risk of DBDPE may be much greater than we expected, due to the high potential to form a variety of dioxin‐like intermediates by microbial oxidation of ethyl group. Therefore, whether it is really safe to replace BDE209 with DBDPE is a debatable question, and more ecotoxicological and health data are needed to clarify this issue.